ANALISIS NILAI PERUSAHAAN SUB SEKTOR RETAIL TRADE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siti Hanipah (2021)
This study to determine the effect of profitability, liquidity and interest rate on firm value. Profitability proxied with Return on Equity, Liquidity with Current Ratio and Interest Rate by BI Rate. Population in this study were Retail Trade Sub Sector listed in Indonesia Stock Exchange period of 2016-2019. Technique sampling used was purposive sampling and obtained 9 retail trade sub sector companies with research period of four to obtained 36 units of sample. Data analysis technique using Panel Data Regression Analysis with E-views 10 and significant level of 5%. The result of this study show that (1) profitability has a significant positive effect on firm value, (2) liquidity has no significant effect on firm value, and interest rate has no significant effect on firm value.